2021
DOI: 10.1029/2021jc017172
|View full text |Cite
|
Sign up to set email alerts
|

Local‐ and Large‐Scale Drivers of Variability in the Coastal Freshwater Budget of the Western Antarctic Peninsula

Abstract: The west Antarctic Peninsula (WAP; Figure 1) is a region characterized by pronounced climatic variability. Its atmosphere has warmed rapidly since the middle of the last century with significant periods of cooling superposed (Smith et al., 1996;Turner et al., 2016;Vaughan et al., 2003). These changes sit within a broader pattern of warming over many parts of West Antarctica over the past 30-50 years, with little overall change

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 76 publications
0
12
0
4
Order By: Relevance
“…An analytical reproducibility of ± 0.02‰ was obtained with duplicate analysis. Using δ 18 O and surface salinity data, we quantitatively separated sea ice melt from meteoric water (glacial melt, precipitation, and runoff from snow melt) by solving a three‐endmember mass balance equation ( see methods and endmember values in Meredith et al 2021). Using this mass balance equation, negative values for sea ice melt are possible and are indicative of net sea ice formation (i.e., more sea ice grew in situ than melted in situ due to lateral advection).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analytical reproducibility of ± 0.02‰ was obtained with duplicate analysis. Using δ 18 O and surface salinity data, we quantitatively separated sea ice melt from meteoric water (glacial melt, precipitation, and runoff from snow melt) by solving a three‐endmember mass balance equation ( see methods and endmember values in Meredith et al 2021). Using this mass balance equation, negative values for sea ice melt are possible and are indicative of net sea ice formation (i.e., more sea ice grew in situ than melted in situ due to lateral advection).…”
Section: Methodsmentioning
confidence: 99%
“…Using this mass balance equation, negative values for sea ice melt are possible and are indicative of net sea ice formation (i.e., more sea ice grew in situ than melted in situ due to lateral advection). Glacial meltwater discharge is a dominant meteoric source in the coastal and nearshore regions of the WAP (Meredith et al 2013(Meredith et al , 2017(Meredith et al , 2021, but here we will continue to refer to this derived metric as "meteoric water" to explicitly reflect the fact that it comprises both precipitation and glacial meltwater inputs.…”
Section: Ancillary Datamentioning
confidence: 99%
“…In the NAP region, specifically, several studies have reported an increasing contribution of small cryptophytes to the phytoplankton community composition (e.g., Mendes et al, 2013; Mendes, Tavano, Dotto, et al, 2018; Mendes, Tavano, Kerr, et al, 2018), with our decadal in situ dataset suggesting a niche segregation between cryptophytes and diatoms based on physical and chemical properties of the water‐column (Figure S2). The variation in upper ocean physical structures caused by the influence of glacial meltwater input (lower‐salinity waters), which leads to shallower‐stabilized upper layers (Meredith et al, 2021), apparently does not favor the development of diatom bloom (Costa et al, 2021), leaving the well‐lit surface waters free for cryptophytes to grow (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Using this approach, Meredith et al [67] produced new insight into the relative importance of different freshwater inputs to the West Antarctic Peninsula region, an area of very strong climatic sensitivity, and how this importance varies across a range of spatial and temporal scales. Collaborating with the French WAPITI team, Akhoudas et al [68] used δ 18 O to reconcile different quantifications of AABW production and export produced previously using contrasting techniques.…”
Section: (Ii) Tracing Freshwater Inputs With Oxygen Isotopesmentioning
confidence: 99%